2011
DOI: 10.1007/s10029-011-0798-9
|View full text |Cite
|
Sign up to set email alerts
|

International guidelines for prevention and management of post-operative chronic pain following inguinal hernia surgery

Abstract: Purpose To provide uniform terminology and definition of post-herniorrhaphy groin chronic pain. To give guidelines to the scientific community concerning the prevention and the treatment of chronic groin and testicular pain. Methods A group of nine experts in hernia surgery was created in 2007. The group set up six clinical questions and continued to work on the answers, according to evidencebased literature. In 2008, an International Consensus Conference was held in Rome with the working group, with an audien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
257
2
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 362 publications
(279 citation statements)
references
References 57 publications
4
257
2
16
Order By: Relevance
“…The initial retrospective results from the TULIP group did not identify a difference in the rate of chronic pain (4.4 % TIPP versus 4.1 % Lichtenstein) [4]. Furthermore, while the results of the randomized, prospective TULIP trial demonstrated a significant difference, a 12.9 % rate of chronic pain for a Lichtenstein repair is far from enviable and far exceeds their prior results of 4.1 % or the ideal rate of 0.5 % achievable with three nerve identification and proper nerve handling [3][4][5].In this study, the authors report excellent outcomes and commendable QOL data but VAS scores were obtained only to postoperative day 30. The follow-up period is too short to draw any broader comparisons to established methods such as Lichtenstein and TEP that have well established, reproducible long-term data on outcomes including QOL, recurrence, and chronic pain.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…The initial retrospective results from the TULIP group did not identify a difference in the rate of chronic pain (4.4 % TIPP versus 4.1 % Lichtenstein) [4]. Furthermore, while the results of the randomized, prospective TULIP trial demonstrated a significant difference, a 12.9 % rate of chronic pain for a Lichtenstein repair is far from enviable and far exceeds their prior results of 4.1 % or the ideal rate of 0.5 % achievable with three nerve identification and proper nerve handling [3][4][5].In this study, the authors report excellent outcomes and commendable QOL data but VAS scores were obtained only to postoperative day 30. The follow-up period is too short to draw any broader comparisons to established methods such as Lichtenstein and TEP that have well established, reproducible long-term data on outcomes including QOL, recurrence, and chronic pain.…”
mentioning
confidence: 98%
“…The initial retrospective results from the TULIP group did not identify a difference in the rate of chronic pain (4.4 % TIPP versus 4.1 % Lichtenstein) [4]. Furthermore, while the results of the randomized, prospective TULIP trial demonstrated a significant difference, a 12.9 % rate of chronic pain for a Lichtenstein repair is far from enviable and far exceeds their prior results of 4.1 % or the ideal rate of 0.5 % achievable with three nerve identification and proper nerve handling [3][4][5].…”
mentioning
confidence: 98%
See 3 more Smart Citations